2019
DOI: 10.1093/mnrasl/slz174
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of a sudden change of spectral appearance or magnetic field strength of the O9.7V star HD 54879

Abstract: It was recently claimed that the magnetic O-type star HD 54879 exhibits important radial velocity variability indicative of its presence in a spectroscopic binary. More remarkably, it was furthermore reported that the star underwent a short, sudden variation in spectral type and magnetic field. In this Letter we examine new Narval and ESPaDOnS data of this star in addition to the previously-published FORS2 data and conclude that both the reported velocity variations and the sudden spectral and magnetic changes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We have seven stars with a clear magnetic field detection in the literature, namely HD 37061 (Shultz et al 2019a), HD 57682 (Grunhut et al 2009(Grunhut et al , 2012, HD 54879 (Castro et al 2015;Shenar et al 2017;Hubrig et al 2019;Wade et al 2020a), HD 37022 (Donati et al 2002;Wade et al 2006), HD 37742 (Bouret et al 2008;Blazère et al 2015), HD 46056 (Grunhut et al 2017;Petit et al 2019), and HD 37479 (Landstreet & Borra 1978;Oksala et al 2012;). In all LS-periodograms singular frequencies are visible in the low frequency regime (ranging between 0.31 and 1.67 d −1 , with amplitudes between 0.11 and 6.6 mmag).…”
Section: Magnetic O-and B-type Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have seven stars with a clear magnetic field detection in the literature, namely HD 37061 (Shultz et al 2019a), HD 57682 (Grunhut et al 2009(Grunhut et al , 2012, HD 54879 (Castro et al 2015;Shenar et al 2017;Hubrig et al 2019;Wade et al 2020a), HD 37022 (Donati et al 2002;Wade et al 2006), HD 37742 (Bouret et al 2008;Blazère et al 2015), HD 46056 (Grunhut et al 2017;Petit et al 2019), and HD 37479 (Landstreet & Borra 1978;Oksala et al 2012;). In all LS-periodograms singular frequencies are visible in the low frequency regime (ranging between 0.31 and 1.67 d −1 , with amplitudes between 0.11 and 6.6 mmag).…”
Section: Magnetic O-and B-type Starsmentioning
confidence: 99%
“…Subsequent studies have shown that the magnetic and spectroscopic variability implies a long rotation period (Shenar et al 2017). A recent sudden change in magnetic field, accompanied by radial velocity variations on the time-scale of days was claimed by Hubrig et al (2019) but this has been contested by Wade et al (2020a). The one-sector TESS data set shows low amplitude stochastic variability.…”
Section: Appendix B42: Magnetic O-and B-type Starsmentioning
confidence: 99%